Mechanisms of protein folding reactions - Kiefhaber, Thomas (Henry Stewart Talks, 2007)
History of protein folding, Origin of complexity in protein folding kinetics, Slow reactions coupled to folding, Prolyl isomerization, Non-prolyl isomerization, Association reactions, Detection of folding intermediates, Discrimination between different kinetic mechanisms, Folding of multi-domain proteins
Reviewed at 2015/10/27